Space-time coordination dynamics in basketball: Part 1. Intra- and inter-couplings among player dyads - Bourbousson, J.; Sève, C.; McGarry, T. (Journal of Sports Sciences, 2010)
We examined space-time patterns of basketball players during competition by analysing movement data obtained from six game sequences. Strong in-phase relations in the longitudinal (basket-to-basket) direction were observed for all playing dyads, especially player-opponent dyads matched for playing position, indicating that these movements were very constrained by the game demands. Similar findings for in-phase relations were observed for the most part in the lateral direction, the main exception being dyads comprising the two wing players from the same team. These dyads instead demonstrated strong attractions to anti-phase, a consequence perhaps of seeking to increase and decrease team width in tandem. Single instances from select dyads and game sequences demonstrated further evidence of phase stabilities and phase transitions on some occasions. Together, these findings demonstrate that space-time movement patterns of playing dyads in basketball, while unique, nonetheless conform to a uniform description in keeping with universal principles of dynamical self-organizing systems as hypothesized.